Application of Financial Literacy to Elementary School Students to Be More Prosperous in the Future - Ramadhan, Fikry Nurul; Muktiarni, M; Azizah, Nissa Nur; Mupita, Jonah (Universitas Pendidikan Indonesia (UPI), 2022)
Indonesia has almost 2 years in implementing distance learning to prevent an increase in the transmission of the Corona Virus. With the creation of the Thematic community service program, it is hoped that it can increase student interest in learning and help educators and parents of students to facilitate the implementation of online learning activities. This research was conducted in an elementary school in West Java. At the initial stage, the research was conducted to survey the number of students in grade 6 of the Elementary School. The number of students recorded was 60 students in grade 6. Then we distributed the 60 students with 47.60% (21 male students) and 52.40% (39 female students). Learning and teaching activities at Karanganyar State Elementary School 2 are carried out online. The learning media used are Zoom Meet, WhatsApp group, and Google Form for students. This method is a solution in implementing distance learning with interactive learning media. The results of the research show that the average post-test score of 84.0% is greater than the average pre-test score of 49.03%, so the difference is 1.95%. Therefore, we can increase interest, knowledge, and application in material related to financial literacy. This increase in understanding can be done by continuously teaching and giving examples of financial literacy to students through fun media, such as animated videos containing financial literacy.